2019
DOI: 10.3389/fimmu.2019.02348
|View full text |Cite
|
Sign up to set email alerts
|

Bifidobacterial Dialogue With Its Human Host and Consequent Modulation of the Immune System

Abstract: Since bifidobacteria are among the pioneering colonizers of the human infant gut, their interaction with their host is believed to start soon following birth. Several members of the Bifidobacterium genus are purported to exert various health-promoting effects at local and systemic levels, e.g., limiting pathogen colonization/invasion, influencing gut homeostasis, and influencing the immune system through changes in innate and/or adaptive immune responses. This has promoted extensive research efforts to shed li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
114
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(120 citation statements)
references
References 102 publications
(137 reference statements)
2
114
0
4
Order By: Relevance
“…Despite this limitation in performing a straightforward comparison between findings of different studies, key bacterial players have transversely been found in feline and canine faeces in different studies, regardless of the metagenomic approaches used. Specifically, Fusobacteria, Bacteroidetes and Firmicutes were identified as the predominant and prevalent bacterial phyla characterizing the faecal microbiota of dogs and cats (Ritchie et al ., 2010; Handl et al ., 2011; Minamoto et al ., 2012; Tun et al ., 2012; Alessandri et al ., 2019a–c). Within the Firmicutes phylum, Bacilli, Clostridia and Erysipelotrichi are the most representative bacterial classes for both canine and feline gut microbiota.…”
Section: Insights Into the Gut Microbiota Of Healthy Dogs And Catsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite this limitation in performing a straightforward comparison between findings of different studies, key bacterial players have transversely been found in feline and canine faeces in different studies, regardless of the metagenomic approaches used. Specifically, Fusobacteria, Bacteroidetes and Firmicutes were identified as the predominant and prevalent bacterial phyla characterizing the faecal microbiota of dogs and cats (Ritchie et al ., 2010; Handl et al ., 2011; Minamoto et al ., 2012; Tun et al ., 2012; Alessandri et al ., 2019a–c). Within the Firmicutes phylum, Bacilli, Clostridia and Erysipelotrichi are the most representative bacterial classes for both canine and feline gut microbiota.…”
Section: Insights Into the Gut Microbiota Of Healthy Dogs And Catsmentioning
confidence: 99%
“…In addition, the observation that differences in the proportion of macronutrients in the canine and feline diet cause gut microbiota compositional changes was confirmed from a functional point of view. Indeed, a shotgun metagenomics analysis involving a faecal sample per group of diet (commercial diet vs. BARF) revealed a higher abundance of GH families involved in the breakdown of complex plant‐derived polysaccharides being associated with a commercial food diet, while a greater proportion of genes involved in amino acid degradation and fatty acid/lipid degradation pathways was observed in the faecal samples from dog fed on a diet of raw meat (Alessandri et al ., 2019a–c). In parallel, the RMBD was shown to play a role in modulating the intestinal metabolome as a BARF‐based diet causes an increase in faecal cholesterol and other metabolites, such as isomaltose, the inhibitory neurotransmitter gamma‐aminobutyric acid (GABA) and its precursor gamma‐hydroxybutyric acid (GHB; Schmidt et al ., 2018).…”
Section: The Effect Of Changes In Dietary Habits On Canine and Felinementioning
confidence: 99%
See 1 more Smart Citation
“…Other enzymes such as N-acylated homoserine lactone (AHL)-lactonase help modulate the structure of the microbiota by decreasing the quorum-sensing of pathogenic bacteria [19]. Several secreted proteins act as essential mediators for the establishment of a bifidobacteria-host immune system dialogue [20]. However, no study has been conducted to examine the total secretome of the gut microbiota, and most importantly, what is the expressed secretome codified in the metatranscriptome of the human gut microbiome.…”
Section: Introductionmentioning
confidence: 99%
“…Bifidobacteria are among those bacteria that are currently widely used as probiotics and that are capable of interacting with the immune system (Villeger et al, 2019). A growing number of studies have highlighted bifidobacteria as commensal organisms capable of stimulating and modulating specific pathways, through which they influence the host immune responses, both innate and adaptive (Palmer et al, 2007;Arboleya et al, 2016;Hidalgo-Cantabrana et al, 2017;Pickard et al, 2017;Ruiz et al, 2017;Alessandri et al, 2019). In fact, various strains of Bifidobacterium individually or in combination with other strains have been evaluated as probiotics for different diseases and some of these have shown quite promising results in alleviating the symptoms of IBD, IBS, diarrhoa and allergy (Tojo et al, 2014).…”
Section: Bifidobacterial Immunomodulatory Effectsmentioning
confidence: 99%